CHANGES IN COLORRETAL CANCER PARADIGMS: THE REASONS FOR INCREASED INCIDENCE AND OCCURRENCE IN YOUNG AGE GROUPS (CIPEEX, 2022)
COLORECTAL CANCER IS, NOWADAYS, THE THIRD MOST INCIDENT AND SECOND MOST LETHAL NEOPLASIA IN THE WORLD. TAKEN, UNTIL LATELY, AS AN ILLNESS TYPICAL FOR THE ELDERLY, IT IS IMPRACTICABLE TO IGNORE ITS INCREASE IN YOUNGER POPULATIONS, TO THE DETRIMENTO OF THE LATTER. THEREFORE, THIS WORK AIMS TO EVALUATE THE POSSIBLE REASONS FOR SUCH CHANGE. IT IS A LITERATURE REVIEW BASED UPON THE DATABASES SCIELO, PUBMED, EUROPE PMC AND GOOGLE SCHOLAR, UNDER THE GIVEN KEYWORDS: CANCER COLORRETAL E INCIDNCIA, AND ITS ENGLISH CORRESPONDENTS€‹ COLORECTAL CNCER AND €‹INCIDENCE, HAVING BEEN SELECTED, IN THE END, THE 20 ARTICLES BEST ADEQUATE TO THE THEME OF THE STUDY. BEYOND THAT, READINGS OF THE NATURE GENETICS AND JOURNAL PLOS GENETICS PERIODICS, AND OF THE INCA AND BRITISH SOCIETY OF GASTROENTEROLOGY WEBSITES WERE MADE. AS FOR THE RESULTS, IT WAS FOUND THAT, WHILE THE NUMEROUS BEHAVIOR RELATED RISK FACTORS, AND ITS PATHOLOGICAL CONSEQUENCES, ARE IN NA INCREASE RATE FOR THE YOUTH, THE SCREENING RATES HAVE REMAINED STAGNANT FOR THEM, HAVING, AT THE SAME TIME, RISEN FOR THE LATER AGE. ALTHOUGH THE ARTICLES RECOGNIZE THAT, FOR THE LACK OF RESEARCH DESTINED TO THE MATTER, IT IS NOT A CERTAINTY, THAT IS THE MOST PROBABLE CAUSE TO THE RISE IN CASES OF THE DISEASE IN THE YOUTH. THUS, IT IS CONCLUDED THAT LIFESTYLE AND ITS ASSOCIATED ILLNESSES, ALTOGETHER WITH THE LACK OF SCREENING, ARE, LIKELY, RESPONSIBLE FOR THE INCREASE OF COLORECTAL CANCER IN MORE JUVENILE INDIVIDUALS.
Keywords: Colorectal cancer. Young. Change. Risk Factors. Screening.